Antimicrobial activity of chitosan and combination with antibiotics against mastitis-causing pathogens - Huynh, Thi Kieu Oanh; Pham, Thi Minh Khanh; Huynh, Thuc Quyen; Tran, Van Ty; Nguyen, Quynh Thuong; Ngo, Hong Phuong; Nguyen, Phuong Thao; Nguyen, Thi Thu Hoai (Vietnam Journal of Biotechnology, 2024)
Bovine mastitis (BM), primarily caused by bacterial pathogens infecting mammary glands, stands as the most prevalent disease in dairy cattle. Traditionally, antibiotics have been the primary choice of treatment, yet their overuse has led to widespread resistance and the presence of antibiotic residues in dairy products. Today, chitosan has emerged as a promising alternative in dairy farming. In this study, we systematically screened and assessed the antibacterial efficacy of five chitosan preparations of different viscosities and components. Additionally, we explored the synergistic antimicrobial potential of the most potent chitosan sample in combination with commonly employed antibiotics, including ampicillin, amoxicillin, oxacillin, and levofloxacin against four prevalent BM-causing pathogens: Staphylococcus epidermidis, Streptococcus agalactiae, Streptococcus uberis and Pseudomonas sp. Agar well diffusion, micro-dilution, and checkerboard techniques were applied to assess the antimicrobial activity and interaction effect. Results indicated that, at a concentration of 1%, low and medium viscosity samples (samples 1, 2, 3) exhibited relatively low activity, compared to very low viscosity ones (samples 4, 5). Notably, sample 5, a combination of chitosan sample 1 with orange and grapefruit essential oils, demonstrated the most potent antibacterial activity with a minimal inhibitory concentration (MIC) of 19.53 mg/L against S. agalactiae, S. uberis and S. epidermidis and 78.13 mg/L against Pseudomonas sp.. Furthermore, the combination of this chitosan sample and antibiotics exhibited some synergistic interactions against BM-causing pathogens, as indicated by the fractional inhibitory concentration (FIC) values ranging from ≥ 0.5 to ≤ 1. While these effects were notable, they did not reach the threshold for strong synergism (FIC < 0.5). In summary, our study highlighted the high antibacterial activity of low viscosity chitosan, particularly in combination with essential oils. Although there were observed synergistic effects with antibiotics against BM-causing pathogens, the strength of these interactions was not robust enough to conclusively categorize them as strongly synergistic. Chitosan, however, emerges as a promising agent in the ongoing exploration of alternatives to antibiotics in the management of BM in dairy farming.